2016
DOI: 10.1016/j.archger.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ageing effects on muscle tone and mechanical properties of rectus femoris and biceps brachii in healthy males and females using a novel hand-held myometric device

Abstract: Please cite this article as: Agyapong-Badu, Sandra, Warner, Martin, Samuel, Dinesh, Stokes, Maria, Measurement of ageing effects on muscle tone and mechanical properties of rectus femoris and biceps brachii in healthy males and females using a novel hand-held myometric device.Archives of Gerontology and Geriatrics http://dx.doi.org/10. 1016/j.archger.2015.09.011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
140
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 38 publications
14
140
5
2
Order By: Relevance
“…Bias induced by this variability cannot be completely ruled out but is an undeniable and essential clinical presentation of dementia patients with paratonia. Although it is suggested that a series of 10 taps is sufficient for Myoton measurement [21], van Deun et al [22] …”
Section: Reproducibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Bias induced by this variability cannot be completely ruled out but is an undeniable and essential clinical presentation of dementia patients with paratonia. Although it is suggested that a series of 10 taps is sufficient for Myoton measurement [21], van Deun et al [22] …”
Section: Reproducibilitymentioning
confidence: 99%
“…An upper limb is also affected earlier by paratonia than a lower limb [1]. Because of the importance in upper arm functionality, the m. biceps brachii was also used in other Myoton studies [11,12,15,16,19,21,22].…”
Section: Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio a max · m /Δl describes the dynamic stiffness of the tissue (N/m). Natural log of maximum displacement (tissue resistance measured in mG) divided by maximum displacement of the second period of oscillation which takes place due to the recuperation of stored residual mechanical energy in tissue expresses the dampening ratio due to the dissipation of mechanical energy in the tissue during one oscilla-tion cycle (Gavronski et al 2007;Agyapong-Badu et al 2016). …”
Section: Parameters Measuredmentioning
confidence: 99%